(untitled) (International Journal of Design (INJUDES), 2021)
In George Town Heritage City, there is a perception that the styles of the shophouses were influenced by the western and eastern cultures but how far regarding the definition and origin of the name â€œshophousesâ€ and significance of the interior architectural identity design are yet to receive in-depth research in Malaysia. Therefore, this paper appraises the definition of shophouses in the region with an emphasis on the significance of the interior architectural identity design. This has become necessary because the shophouse is one of the key components that enhanced the city to be enlisted in the UNESCO World Heritage list in 2008. To achieve the main aim, observation, case studies, and secondary sources were combined in the study. Findings show that the significance of the interior architectural identity design regarding the definition of shophouses has been silent in the literature and was addressed as part of the paperâ€™s implications. Also, the emerged findings will be relevant to stakeholders because the definition revealed the significance of interior architectural identity design as one of the architectural components that influence and govern shophouses design.